Chiltons guide to small appliance repair and main - Williams, Gene B. (Pennsylvania Chilton Book Company, 1986)
Small home appliances have often been touted as "labour-saving devices". Salespeople and advertisements usually tell consumers how much time and energy they can save each day by using these handy little helpers. The pitch is that houshold appliances simplify chores.
Keywords: Reference